MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENERAPKAN MODEL PEMBELAJARAN TUNTAS PADA SISWA KELAS IV SDN DONAN 04 KEC. CILACAP TENGAH TAHUN PELAJARAN 2017/2018 - Farida hayatun (Pusat Studi Pendidikan dan Kreativitas Guru, 2020)
The teaching method used by the teacher in teaching and learning activities must be adjusted to the formulation of learning objectives. Teaching and learning activities require mental involvement and student work. The problems examined in this study are: (a) Can the application of a complete learning model improve student achievement in Islamic Religious Education subject matter? (b) How is the effect of the complete learning model in increasing the motivation to learn Islamic Religious Education? To improve student achievement and motivation in learning Islamic Religious Education, at SDN Donan 04 Kec. Central Cilacap, one of which is by applying a thorough learning model. By applying this learning method it is hoped that the achievement and motivation to learn Islamic Religious Education can increase. The objectives of this action research are: (a) Knowing the increase in learning achievement of Islamic Religious Education after the application of a complete learning model. (b) Knowing the effect of the complete learning model in increasing learning achievement and motivation on the subject matter of Islamic Religious Education. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I (66.67%), cycle II (75.56%), cycle III (86.67%). The conclusion of this study is that the complete learning model can have a positive effect on student achievement and learning motivation at SDN Donan 04 Kec. Central Cilacap 2017/2018 school year. This learning model can be used as an alternative to learning Islamic religious education.